The Effectiveness of Psychoreligious Therapy: Murottal Al Qur'an on Chest Pain Level of the Patient in Intensive Care Unit - Priyanto Priyanto; Achmad Fauzi Kamal; Debie Dahlia; Idia Indar Anggraeni (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Chest pain is the main complaint felt by patients with coronary heart disease. Chest pain occurs during a heart attack when oxygen supply to the myocardium is decreased. Psychoreligious therapy: murottal Al-Qur'an is a psychoreligious therapy given to patients by listening to verses of the Qur'an for a few minutes to have a positive impact on the patient's psychological condition, thereby providing a relaxing effect to reduce pain. This study aims to determine the effectiveness of psychoreligious therapy: murottal Al-Qur'an on the level of chest pain. This research design used pre-experimental method with one group pre and post-test design. The population of this study were patients with coronary syndrome acute who were treated in the Intensive Care Unit of the Tidar General Hospital Magelang. The sampling technique used accidental sampling, with a total of 34 respondents. The research instrument used the Numeric Rating Scale to measure the scale of chest pain before and after therapy. Psychoreligious therapy: murottal Al-Qur'an given according to standard operating procedures for 20 minutes. The statistical test used paired t test. The results showed that there was a significant difference from chest pain level before and after psychoreligious therapy: murottal Al-Qur'an with p-value 0.000 (p<α (0.05)). Psychoreligious therapy: murottal Al-Qur'an can effectively reduce the scale of the patient's chest pain. There is a need for socialization and application of psychoreligious therapy: murottal Al-Qur'an as a therapeutic modality and further research is needed on various psychoreligious therapies that are useful in nursing care services in hospitals.